Overview of prokaryotic molecular chaperones - Houry, Walid A. (Henry Stewart Talks, 2007)
Protein folding in vitro versus in vivo, Concept of a molecular chaperone, Chaperones in E. coli, Trigger factor, DnaK/DnaJ/GrpE system, GroEL/GroES system, Clp ATPases
Archived at 2020/08/13